Effectiveness Of Snakefish And Chicken Breast In The Process Of Post Caesar Operation Wound Healing At Kuala Penguang Hospital - Heni sugiyarti (Universitas STRADA Indonesia, 2025)
One of the healing processes for post-cesarean wounds is through improving nutrition by consuming foods high in calories and protein, such as fish, eggs, meat, shrimp, shellfish, cheese, liver, milk, peanuts, red beans, green beans, soybeans, tempeh and tofu. . This research aims to analyze the effectiveness of administering snakehead fish and chicken breast in healing post-Caesarean section wounds. This research uses a quasi-experimental research design with a two group post test design with control groups approach. The population in this study were all mothers who gave birth by caesarean section at Kuala Pembuang Regional Hospital. Using a purposive sampling technique, a sample of 30 respondents was obtained. The independent variable was consumption of snakehead fish and chicken breast using SOP and the dependent variable was wound healing using observation, using the Mann Withney statistical test. The results of the research from 10 respondents, the majority of respondents who consumed snakehead fish, 6 (60%) respondents had post-operative wounds not yet closed, from 10 respondents it was found that most respondents consumed chicken breast, 6 (60%) respondents had post-operative wounds not yet closed, while 10 respondents Most of the control group, namely 6 (60%) respondents, had their post-operative wounds closed on the 7th day. Mann Witney's statistical test results showed ap value of 0.383 > 0.005, so H0 was accepted, and H1 was rejected, meaning snakehead fish and chicken breast were not effective in the healing process. post caesarean wound. Snakehead fish and chicken breast contain quite high levels of protein so they can speed up the healing of post-cesarean section wounds, so it is hoped that post-cesarean mothers consume high protein sources. Snakehead fish and chicken breast contain quite high protein so that they can speed up the healing of post-cesarean wounds, so it is hoped that post-cesarean mothers will consume high protein sources.